Notes on the Nesting Behavior of Four Solitary Wasps (Insecta: Hymenoptera) in India - Phong, Pham Huy; Dinh, Nguyen Thi; Kumar, P. Girish (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 2DO - 10.25073/2588-1140/vnunst.5608, 2024)
India is one of countries that has the highest biodiversity level of Hymenoptera in the Oriental region, as well as in the world. Hence, studies of its biology have received a large consideration of entomologists. In a course of study on Hymenoptera in Odisha state of the country in 2015, we observed the nesting behavior of several wasps and recorded their new nesting sites. Therefore, this study presents notes on the nesting behavior of the four Indian wasps, namely, Chalybion bengalense (Dahlbom) (Sphecidae), Trypoxylon petiolatum F. Smith (Crabronidae), Delta esuriens (Fabricius) and Xenorhynchium nitidulum (Fabricius) (both, Vespidae: Eumeninae). The first two wasps used man-made holes on the walls of a big temple for their nesting sites, fully stored paralyzed spiders in the nest cells for offspring and plugged them with mud, in a case of Chalybion bengalense , females added a white layer of unknown material on the outside surface of covers. Delta esuriens chose its nesting site beneath the thatched roof of a human house, built a linear series of pot-shaped mud cells that were firmly attached to some rice blades hung loosely beneath the roof and provisioned caterpillars in these nest cells. The latter built a mud nest on a wall of a human house. Xenorhynchium nitidulum made a nest cell oblique a 30° angle from the vertical surface of the wall, plastered the outside surface of the cell with tree resin of a certain plant species after completion of building and then stored prey of an unknown caterpillar in the cell. The female of Xenorhynchium nitidulum sit in the nest cell after provisioning of the first prey to the following morning suggesting that the wasp progressively provisions its nest and the egg is laid prior to provisioning.